EFEKTIVITAS PELAYANAN PENGUJIAN KENDARAAN BERMOTOR MELALUI SISTEM DRIVE THRU DI DINAS PERHUBUNGAN KABUPATEN SIDOARJO - Retno Dwi Ariyanti; Diana Hertati (Jurnal Penelitian Administrasi Publik, 2019)
This research is based on the desire of the Transportation Office Sidoarjo to improve services to the community, one of them is tesing of motorized vehicles. To realize an easy motorized testing service, the Trasnportation Office Sidoarjo innovates with motorized vehicle testing services through Drive Thru system. The purpose of this research is to describe and analyze the effectiveness of motorized vehicle testing services through the Drive Thru System at Transportation Office Sidoarjo using qualitative research methods with observation data collection techniques, interviews, documentation, and data condensation, data presentation adn data conclusion. The location of this reasearch is at the Transportation Office Sidoarjo. The result obtauned are : (1) the time factor has been effective but not maximal. (2) The accuracy factor produuced is effective. (3) Service Provider Style factors which are given is effective. Keyword : Effectiveness, Drive Thru System